President Trump and the Virtue of Power - Jérôme Viala-Gaudefroy (Revue LISA)
As the “story-teller-in-chief” of the nation, the American president plays a key role in defining national identity. Traditionally, American presidents have talked about the nation through the heroic myths of power and virtue, two distinct features at the heart of American exceptionalism. This narrative has been greatly altered by President Donald Trump who has repudiated the moral vision of his predecessors. This does not mean, however, that this president has no moral vision of his own. The present study of President Trump’s speeches, remarks and tweets, reveals a consistent narrative in which power has been fused with virtue. Donald Trump has turned Christianity into a cultural expression of power and American exceptionalism has been reduced to the assertion of national pride, strength and sovereignty. The nationalistic nature of Trump’s rhetoric is characterized by the use of patriotic symbols such as blood, flag and family. This nationalism evokes a vision of the world that is no longer a community of nations working together for a liberal order, but rather an arena in which hyper-individualized sovereign nations compete with each other. Last, the president’s discourse articulates the myth of violent power through the use of war and game metaphors. Donald Trump’s populist expression of this virtue of power can be traced back to his own personal background as well as political strands of populism that have regularly surged in American history.